Validation of the analysis method for marker compound ellagic acid of ethanol extracts of Sanguisorba officinalis L. using HPLC-DAD - YIM, Soon-Ho; KANG, Seok-Jun; SEON, Ho-Young; BYUN, Na-Young (Food Science and Technology, 2023)
The validation of ellagic acid as a marker compound was attempted as an analysis method for the standardization of the extract from Sanguisorba officinalis L. for the development of healthy functional foods. The ellagic acid analysis using high-performance liquid chromatography with diode-array detection (HPLC-DAD) and retention time with standard compounds satisfied the stay time and specificity. Ellagic acid has confirmed limit of detection (LOD), limit of quantitation (LOQ), accuracy, precision, recovery rate, stability, and content analysis by HPLC for an 80% ethanol extract of Sanguisorba officinalis L. The correlation (R2) at the concentration of ellagic acid of 9.5–95.0 µg/mL was above 0.999, showing high linearity. The LOD and LOQ were expressed as 1.5430 and 4.6757 μg/mL, respectively. The recovery rate was 99 to 110%. The precision of RSD intraday was 0.23–0.65% and interday was 0.18–2.13%. In addition, the average recovery rate of ellagic acid before and after 24 h was 98.79%, confirming a change in the content of 0.17%, and the content of ellagic acid was 22.48 µg/mL in 80% ethanol extract of Sanguisorba officinalis L.